2007
DOI: 10.1002/ppap.200730606
|View full text |Cite
|
Sign up to set email alerts
|

High Rate Deposition of Al2O3 Coatings Reactively Sputter Deposited

Abstract: According to its high temperature stability, low friction coefficient against metals and relatively high hardness, α‐Al2O3 is a good candidate for high performance coatings. However, Al2O3 is brittle which limits its application as a protective coating for mechanical applications. Moreover, reactive sputtering of alumina is often associated with low deposition rates. In this study, two experimental devices were used to deposit Al2O3 coatings with high deposition rates. High bias voltage, as well as an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This was suggested by Mercs et al in the case of the deposition of Al 2 O 3 thin films by reactive magnetron sputtering from a hot (i.e. not cooled) aluminum target [3], although no quantification of the IR radiation flux was reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This was suggested by Mercs et al in the case of the deposition of Al 2 O 3 thin films by reactive magnetron sputtering from a hot (i.e. not cooled) aluminum target [3], although no quantification of the IR radiation flux was reported.…”
Section: Introductionmentioning
confidence: 97%
“…In most cases, IR emission from the hot target surface is completely ignored as its interaction with the growing film. One of the main reason lie in the difficulty to evidence such energetic contribution by conventional discharge diagnostics [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that T cr of the film decreases and its crystallinity increases when high fluxes of ions ν i are incident at the surface of the growing film. Therefore, reactive ionized magnetron sputtering [13] or reactive high-power pulsed magnetron sputtering [1][2][3]5,[9][10][11][12] has been used in many experiments. Also, a low-temperature formation of α-Al 2 O 3 thin films on a crystalline Cr 2 O 3 template has been reported [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…cemented carbides. Therefore, a great effort has been devoted to the search of a process or method which allows the crystallization temperature T cr of the α-Al 2 O 3 phase to be decreased [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%